Faktor-faktor yang Berhubungan dengan Perilaku Pemberian ASI Eksklusif Tenaga Keperawatan di Wilayah Tangerang Selatan - Mustikawati Mustikawati; Yusnita Yusfik; Yannaulli Yannaulli (STIKes Persada Husada Indonesia, 2015)
Exclusive breastfeeding during the first 6 months is very important in accordance with one of the goals of the Millennium Development Goals (MDGs) to reduce child mortality and improving maternal health. Based on the report by the World Breastfeeding Trends Initiative 2012, Indonesia ranks 49 out of 51 countries that support exclusive breastfeeding. Nurses have a very important role especially educative and promotion to the community in providing health education on exclusive breastfeeding. (M.Hamdani, 2013). The purpose of this study to analyze factors associated with exclusive breastfeeding behavior on Nurses in Hospital SouthTangerang area. This study used a cross-sectional approach, namely the measurement of the independentvariables and the dependent variable only once in a while (Nursalam, 2003). The results of bivariate analysisusing Chi-square statistical test with the research of knowledge, level of education, motivation, parity, workenvironment, family support and the support of peers do not have a meaningful relationship with the behavior of exclusive breastfeeding in nursing with a P-values sequentially: P=0.069; P=0.476; P=0.079; P=0.282; P=0.771; P=0.153; P=0.055. While mother interest and quantity of breast milk have a meaningful relationship with the behavior of exclusive breastfeeding in the hospital nursing staff of South Tangerang region, with a value of P values in a row is P=0.049 with OR:3.400 and P=0.001 with OR:7.249.